Improvement of Soilless Media by Incorporation of Trichoderma Inoculant for the Production of Cauliflower - Iberahim, Ismail (2001)
Improvement of soilless media by incorporation of Trichoderma (UPM 23) for the production of cauliflower under Protected Environment Agriculture (PEA) system was attempted. Three soilless media; coconut dust (CD), palm oil empty fruit bunch (EFB) and peat (P) singly and as mixtures; coconut dust + peat (CDP) and palm oil empty fruit bunch + peat (EFBP) were used in the study. The physical, chemical and microbiological properties of these soilless media showed that their properties were suitable for growth of cauliflower and proliferation and survival of Trichoderma. They have good pore size with bulk density within the range of mineral soil (1.0-1.8g/l). CD and CDP have high water availability of 15.18% and 13.99% respectively. However, they have low microbial populations comprising mainly of the genera Penicillium, Aspergillus and Rhicopus. No beneficial microbes were detected The effect of soilless media on survival and proliferation of Trichoderma was carried out by either adding the inoculant as an additive to the soilless media or as bio-seed treatment. Trichoderma population in EFB, EFBP and P was reduced more than 50% after 3 days of application. However, in CD and CDP the reduction was only 16.7 % and 34.7% respectively throughout the 21 days of experimental period. Trichoderma population was higher on the roots after day 10 of sampling, suggesting that the antagonist can colonize the germinating roots and live on the root exudates. Incorporation to soilless media was a better delivery system for the antagonist as it gave better distribution and easy contact with the growing roots. Therefore, CD and CDP were selected as substrates to evaluate the effect of airdried preparation of UPM 23 on growth of cauliflower; applied as additive to germination mixes. Trichoderma inoculant at the rate of 30 x 106 cfu/g dry weight substrate have a significant effect on seed germination and seedling emergence of cauliflower. Seedling emergence was 81.3% and 86 38% in CDTV and CDPTV as compared to 40.36% and 42.63% III CD and CDP respectively. Initial establishment and growth of the seedlings were better in Trichoderma amended media, as shown by the stomatal conductance and net photosynthesis rate However, there was no significant difference III vegetative growth, nutrient status and peroxidase activity between treatments, probably due to the dilution effect of Trichoderma inoculant in the substrate with time The plants were also supplied with full strength Cooper Solution at rate of 600 ml/day